The Optimal Dosage of Fermented Herbal Extract on Growth and Feed Efficiency of Nile Tilapia (Oreochromis niloticus) - Yushinta Fujaya,; Andi Aliah Hidayani,; Dwi Kesuma Sari,; Siti Aslamyah,; Nita Rukminasari,; Abdul Muthalib,; Stevie Cristianto,; Emilia Defista,; Hanafiah Fazhan,; Khor Waiho, (Tropical Life Sciences Research, 2023)
Owing to their availability, cost effectiveness and environmental-friendly nature, plant extracts are promising additives for fish farming. This study aims to determine the optimal dosage of fermented herbal extract (FHE)—composed of Morus alba (33.3%), Curcuma xanthorrhiza (33.3%), and Boesenbergia rotunda (33.3%)—for growth enhancement and feed utilisation efficiency of Oreochromis niloticus fingerlings. Fermentation was conducted using probiotics Lactobacillus casei (Yakult®, Tokyo, Japan) and Saccharomyces cereviceae (commercial baker’s yeast). The FHE was high in flavonoid and alkaloid, vitamin C, potassium, natrium, lipase and protease. Four doses of FHE treatments, namely treatment A (0 mg/kg of feed); treatment B (100 mg/kg of feed); treatment C (300 mg/kg of feed); treatment D (500 mg/kg of feed) were compared. After subjected to 35 days of culture, tilapias subjected to FHE-coated feed exhibited better weight gain (WG), specific growth rate (SGR), and feed efficiency (FE) compared to control. The best dosage that gave the highest growth and feed efficiency was treatment C (300 mg/kg of feed). Furthermore, the feed efficiencies of FHE-incorporated treatments were positively influenced by the increased in length and density of intestinal villi, number of goblet cells, lymphocytes, as well as nutrient retention to support growth. The results of this study indicate that FHE is a promising functional feed additive to stimulate growth and improve feed efficiency in tilapia farming.